Writing Migration through the Body - Bond, Emma (Studies in Mobilities, Literature, and Culture, 2018)
Writing Migration through the Body builds a study of the body as a mutable site for negotiating and articulating the transnational experience of mobility. At its core stands a selection of recent migration stories in Italian, which are brought into dialogue with related material from cultural studies and the visual arts. Occupying no single disciplinary space, and drawing upon an elaborate theoretical framework ranging from phenomenology to anthropology, human geography and memory studies, this volume explores the ways in which the skin itself operates as a border, and brings to the surface the processes by which a sense of place and self are described and communicated through the migrant body. Through investigating key concepts and practices of transnational embodied experience, the book develops the interpretative principle that the individual bodies which move in contemporary migration flows are the primary agents through which the transcultural passages of images, emotions, ideas, memories - and also histories and possible futures - are enacted.